Anxiety and Depression among Breast Cancer Patients Undergoing Treatment in Ghana (African Journal of Biomedical Research, 2020)
Breast cancer patients undergoing radiotherapy often experience severe levels of anxiety and depression within the African context. There is a gap in the research literature from Africa, particularly Ghana, with few studies focusing on depression among patients undergoing radiation treatment. The purpose of the study was to find various interventions for depression and anxiety among breast cancer patients in Ghana. A mixed method study examined breast cancer patients undergoing radiotherapy and their responses through a concurrent triangulation involving an interview with selected professional and a detailed patient survey. In all, 100 patients between the ages of 20-89 completed a questionnaire and individual interviews were held with 6 professionals with a minimum of 5 years of work experience. Themes were generated through open coding of the interview data, while multiple regression was performed to determine the relationship between depression and anxiety with the independent variables. In all, 89% had no family history of breast cancer, and the majority (55%) had the disease duration of one to three years. Almost 95% of patients with breast cancer had anxiety and depression in different categories. This included hair loss, discolored finger nails, cost of treatment, and fear of the unknown. Age and monthly income of patients were statistically significant in predicting the anxiety and depression among the patients. Coping mechanisms are essential for all patients undergoing treatment. This study’s implications will lead to positive change when all stakeholders assist in implementing measures to promote coping strategies for breast cancer patients in Ghana.